BIMBINGAN INDIVIDU SEBAGAI UPAYA UNTUK MENINGKATKAN KEDISIPLINAN MENGIKUTI TATA TERTIB SEKOLAH - purnayasa, nyoman (Journal of Education Action Reseach, 2018)
This research was conducted in SMP Negeri 2 Singaraja on the students of class IX 1in odd semester, academic year 2016/2017 with condition of student discipline still less appropriate with initial data reach 75% .The purpose of this action research study is to know whether the individual guidance model can improve discipline students in following school rules. Data collection method was observation. Data analysis method was descriptive for qualitative data. The result obtained from this research was individual guidance can improve student discipline in following school order. This is evident from the results obtained in the first cycle increased 80% of the initial data. After the individual guidance and improvement on the weaknesses that exist in cycle I was increased from Cycle I to Cycle II up to 98%. Conclusion obtained from this study is individual guidance can improve student discipline in following school rules